NAT1 genetic variation increases asthma risk in children with secondhand smoke exposure. (4th March 2021) - Brooks, Cassandra C.; Martin, Lisa J.; Pilipenko, Valentina; He, Hua; LeMasters, Grace K.; Lockey, James E.; Bernstein, David I.; Ryan, Patrick H.; Khurana Hershey, Gurjit K.; Biagini Myers, Jocelyn M.
Abstract: Objective: We previously reported that children exposed to secondhand smoke (SHS) that carried variants in the NAT1 gene had over two-fold higher hair cotinine levels. Our objective was to determine if NAT1 polymorphisms confer increased risk for developing asthma in children exposed to SHS. Methods: White participants in the Cincinnati Childhood Allergy and Air Pollution Study ( n = 359) were genotyped for 10 NAT1 variants. Smoke exposure was defined by hair cotinine and parental report. Asthma was objectively assessed by spirometry and methacholine challenge. Findings were replicated in the Genomic Control Cohort ( n = 638). Results: Significant associations between 5 NAT1 variants and asthma were observed in the CCAAPS exposed group compared to none in the unexposed group. There was a significant interaction between NAT1 rs13253389 and rs4921581 with smoke exposure ( p = 0.02, p = 0.01) and hair cotinine level ( p = 0.048, p = 0.042). Children wildtype for rs4921581 had increasing asthma risk with increasing hair cotinine level, whereas those carrying the NAT1 minor allele had an increased risk of asthma regardless of cotinine level. In the GCC, 13 NAT1 variants were associated with asthma in the smoke-exposed group, compared to 0 in the unexposed group, demonstrating gene-level replication. Conclusions: Variation in the NAT1 gene modifies asthma risk in children exposed to secondhand-smoke. To our knowledge, this is the first report of a gene-environment interaction between NAT1 variants, smoke exposure, cotinine levels, and pediatric asthma. NAT1 genotype may have clinical utility as a biomarker of increased asthma risk in children exposed to smoke.